PENGARUH GAYA MOTIVASI DAN KEPUASAN KERJA TERHADAP KINERJA PEGAWAI PT. PELNI CABANG MAKASSAR DENGAN KOMITMEN ORGANISASI SEBAGAI VARIABEL INTERVENING - Firdayanti, Erfani; Kadir, Moh. Akob; Jumadi, Edy (Jurnal Bina Bangsa Ekonomika, 2025)
This study aims to determine the direct influence of motivation, job satisfaction and organizational commitment on employee performance. The direct influence of motivation and job satisfaction on job satisfaction. The indirect influence of motivation and job satisfaction variables on employee performance with organizational commitment as an intervening variable in employees of PT. PELNI Makassar Branch. Data collection uses primary data obtained from the questionnaire using saturated samples. The population in this study is 112 respondents. The results of the questionnaire have been tested for validity and reliability by using the PLS model scheme and model evaluation, the evaluation of the inner model with the determinant coefficient test, the goodness test of the model and the hypothesis test both directly and indirectly. The results of this data processing use SmartPLS version 3. The results of the study directly show that the variables of motivation, job satisfaction and organizational commitment have a positive and significant effect on employee performance. Motivation has a positive and significant effect on organizational commitment. Job satisfaction has no effect on organizational commitment. The results of the study indirectly show that work motivation has a positive and significant effect on employee performance with organizational commitment as an intervening variable. Job satisfaction has no effect on employee performance with organizational commitment as an intervening variable